Naphthalimide‐Fused Dipyrrins: Tunable Halochromic Switches and Photothermal NIR‐II Dyes. Issue 19 (17th February 2022) - Maurya, Yogesh Kumar; Chmielewski, Piotr J.; Cybińska, Joanna; Prajapati, Bibek; Lis, Tadeusz; Kang, Seongsoo; Lee, Seokwon; Kim, Dongho; Stępień, Marcin
Abstract: A family of tunable halochromic switches is developed using a naphthalimide‐fused dipyrrin as the core π ‐conjugated motif. Electronic properties of these dipyrrins are tuned by substitution of their alpha and meso positions with aryl groups of variable donor–acceptor strength. The first protonation results in a conformational change that enhances electronic coupling between the dipyrrin chromophore and the meso substituent, leading to halochromic effects that occasionally exceed 200 nm and switch the absorption between the near‐infrared (NIR)‐I and NIR‐II ranges. A NIR‐II photothermal effect, switchable by acid–base chemistry is demonstrated for selected dipyrrins. Further protonation is possible for derivatives bearing additional amino groups, leading to up to four halochromic switching step. The most electron‐rich dipyrrins are also susceptible to chemical oxidation, yielding NIR‐absorbing radical cations and closed‐shell dications. Abstract : Naphthalimide‐fused dipyrrins decorated with aryl groups of variable electron‐donating strength are a new class of tunable near‐infrared dyes that can be switched between near‐infrared (NIR)‐I and NIR‐II absorptions via one or more protonation steps. The NIR‐II absorbing dipyrrinium cations can be employed as halochromic photothermal agents, which can be reversibly activated by addition of an acid or base.